Coseismic Folding During Ramp Failure at the Front of the Sulaiman Fold‐and‐Thrust Belt. Issue 23 (1st December 2022) - Javed, Muhammad Tahir; Barbot, Sylvain; Javed, Farhan; Ali, Aamir; Braitenberg, Carla
Abstract: The Sulaiman Fold Thrust (SFT) in Central Pakistan formed during the India‐Eurasia collision in the late Cenozoic. However, the mechanics of shortening of the brittle crust at time scales of seismic cycles is still poorly understood. Here, we use radar interferometry to analyze the deformation associated with the 2015 magnitude (Mw) 5.7 Dajal blind earthquake at the eastern boundary of the SFT. We use kinematic inversions to determine the distribution of slip on the frontal ramp and of flexural slip along active axial surfaces for the forward‐ and backward‐verging two end‐member models: a double fault‐bend‐fold system and a fault‐propagation‐fold. In both models, a décollement branches into a shallow ramp at approximately 7.5 km depth with coseismic folding in the hanging wall. The Dajal earthquake ruptured the base of the Boundary Thrust buried under the sediment from the Indus‐River floodplain, representing fault‐bend or fault‐propagation folding some 30 km off its nearest surface exposure. Plain Language Summary: The relative motion between tectonic plates is accommodated across wide fault zones that concentrate deformation. Yet, how these deformation zones grow over time is poorly known. In this study, we investigate the Sulaiman Fold‐Thrust (SFT) belt, Pakistan at the plate boundary between the Indian and Eurasian continents. We use radar interferometry to estimate the crustal deformation induced by the 2015 Mw 5.7 Dajal earthquake at the eastern margin of the SFT. The rupture did not reach the surface at the eastern extension of the SFT, buried under the younger sediments of the Indus River floodplain. The rupture and associated folding in the hanging wall documents the eastward growth of the SFT. These observations document the seismic potential of hidden ramps in fold‐and‐thrust belts and the control on final rupture size by fault‐bends and surrounding folds. Key Points: 2015 Mw 5.7 Dajal, Pakistan earthquake ruptured the blind front of the Sulaiman Fold Thrust belt Coseismic deformation includes slip on a blind thrust and flexural slip in the hanging wall The buried section of the Boundary Thrust extends 30 km farther south of the fault trace